2018
DOI: 10.1051/matecconf/201815401045
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of LPG gas leakage based Wireless Sensor Networking

Abstract: Abstract. LPG gas is the main fuel used in households. These days LPG gas leak triggered an accident that resulted in huge losses, especially if the accident occurred within the dense housing. LPG gas leakage monitoring and early detection of a gas leak and a leak warning is needed to prevent more fatal accident. Wireless sensor networking is a technology that can be used to build a centralized monitoring system by using a microcontroller as the interface and control system. This research developed system devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
(2 reference statements)
0
3
0
1
Order By: Relevance
“…Consequently, based on the experiments, they concluded that using a pyroelectric infrared sensor without a Fresnel lens on it enabled them to sense gas leaks at up to 3 m. Conversely, they proved that Markov model use is optimal to detect volatile organic compound gas and process the wavelet transformed sensor data. In addition, Kusriyanto et al [14] developed a device monitoring system and early detection of liquid propane gas (LPG) gas leakage using WSN. To monitor and detect gas leaks early, they used gas sensors of the MQ-4 type and the AVR microcontroller family to control the detecting device.…”
Section: Hardware-based Techniquesmentioning
confidence: 99%
“…Consequently, based on the experiments, they concluded that using a pyroelectric infrared sensor without a Fresnel lens on it enabled them to sense gas leaks at up to 3 m. Conversely, they proved that Markov model use is optimal to detect volatile organic compound gas and process the wavelet transformed sensor data. In addition, Kusriyanto et al [14] developed a device monitoring system and early detection of liquid propane gas (LPG) gas leakage using WSN. To monitor and detect gas leaks early, they used gas sensors of the MQ-4 type and the AVR microcontroller family to control the detecting device.…”
Section: Hardware-based Techniquesmentioning
confidence: 99%
“…With the goal of overcoming these constraints, wireless sensor networks are chosen. The feature that allows sensors to be smart is the seamless and efficient transmission of data that helps alert the user of the current situation (11,(46)(47)(48)(49). Most of the sensing systems developed during the past two decades used no specific wireless communication protocols, transmitting data through standard networks provided by satellites or the Industrial, Scientific and Medical (ISM) bands.…”
Section: Data Communication Systemsmentioning
confidence: 99%
“…Kerentanan selang karet LPG diduga kuat sebagai salah satu penyebab kebakaran (Kusriyanto, 2018;Dewi & Somantri, 2018).…”
Section: Pendahuluanunclassified